2021
DOI: 10.21873/anticanres.15158
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Inflammatory Score Predicts Response and Prognosis in Patients With Lung Cancer Treated With Immunotherapy

Abstract: Aim: This study aimed to investigate useful prognostic factors of immunotherapy in patients with lung cancer. Patients and Methods: We retrospectively observed 73 patients who underwent immunotherapy (nivolumab, pembrolizumab, and atezolizumab) for lung cancer. The systemic inflammatory score (SIS) was calculated as the sum of the following factors scored one point each: Hemoglobin <12.5 g/dl and serum albumin <3.6 g/dl, resulting in scores of 0-2. We examined the correlation between the SIS and initial tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 24 publications
(25 reference statements)
1
28
0
Order By: Relevance
“…It remained uncertain among six cohort studies on the association between pretreatment PNI and DCR for cancer patients treated with ICIs. Pooled analysis revealed that a higher PNI level was associated with greater DCR (pOR = 2.48, 95% CI = 1.87-3.29, Figure 4) (19,20,26,28,29,34). The combined analysis of three studies on the association between PNI and ORR showed that PNI higher than the cutoff indicated more favorable ORR (pOR = 2.17, 95% CI = 1.52-3.10, Figure 5) (26,28,34).…”
Section: Correlation Between Pretreatment Prognostic Nutritional Inde...mentioning
confidence: 98%
See 3 more Smart Citations
“…It remained uncertain among six cohort studies on the association between pretreatment PNI and DCR for cancer patients treated with ICIs. Pooled analysis revealed that a higher PNI level was associated with greater DCR (pOR = 2.48, 95% CI = 1.87-3.29, Figure 4) (19,20,26,28,29,34). The combined analysis of three studies on the association between PNI and ORR showed that PNI higher than the cutoff indicated more favorable ORR (pOR = 2.17, 95% CI = 1.52-3.10, Figure 5) (26,28,34).…”
Section: Correlation Between Pretreatment Prognostic Nutritional Inde...mentioning
confidence: 98%
“…Five publications showed that PNI was an independent predictor of unfavorable PFS in cancer patients with immunotherapy (18,19,26,27,34), whereas five cohort studies detected no significant relationship between PNI and PFS (20,28,30,31,33). The combined analysis of ten studies that enrolled 1,282 participants showed that a higher PNI level was associated with worse PFS (pHR = 1.61, 95% CI = 1.37-1.88, Figure 3).…”
Section: Correlation Between Pretreatment Prognostic Nutritional Inde...mentioning
confidence: 98%
See 2 more Smart Citations
“…Eight studies 16,17,[19][20][21][22][23][24] consisting of 616 patients were included to analyze the association between PNI and PFS. The pooled results showed that patients with low PNI had shorter PFS (HR = 1.75, 95% CI 1.40-2.18, p = 0.000), with no significant heterogeneity (I 2 = 0%, p = 0.638) (Figure 2B).…”
Section: Prognostic Impact Of Pni On Pfsmentioning
confidence: 99%